2014
DOI: 10.1371/journal.pone.0111696
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Trichobilharzia regenti (Digenea: Schistosomatidae) on the Defence Activity of Radix lagotis (Lymnaeidae) Haemocytes

Abstract: Radix lagotis is an intermediate snail host of the nasal bird schistosome Trichobilharzia regenti. Changes in defence responses in infected snails that might be related to host-parasite compatibility are not known. This study therefore aimed to characterize R. lagotis haemocyte defence mechanisms and determine the extent to which they are modulated by T. regenti. Histological observations of R. lagotis infected with T. regenti revealed that early phases of infection were accompanied by haemocyte accumulation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 51 publications
0
6
1
Order By: Relevance
“…), haemocyte peroxidase and phagocytic activities increased again (Amen et al, 1991a;Amen et al, 1992a), whereas Horák and Deme (1998) reported just minor differences between the infected snails and uninfected control L. stagnalis snails in terms of haemocyte phagocytic activity at ten weeks p.i. Contrary to these observations, phagocytic activity and capacity to generate hydrogen peroxide were suppressed in haemocytes from R. lagotis in the patent phase of infection with T. regenti (Skála et al, 2014). Moreover, these haemocytes displayed lower PKC and ERK activity when compared to those from uninfected snails.…”
Section: Immune Responses Of L Stagnalis During T Szidati Infectioncontrasting
confidence: 75%
See 2 more Smart Citations
“…), haemocyte peroxidase and phagocytic activities increased again (Amen et al, 1991a;Amen et al, 1992a), whereas Horák and Deme (1998) reported just minor differences between the infected snails and uninfected control L. stagnalis snails in terms of haemocyte phagocytic activity at ten weeks p.i. Contrary to these observations, phagocytic activity and capacity to generate hydrogen peroxide were suppressed in haemocytes from R. lagotis in the patent phase of infection with T. regenti (Skála et al, 2014). Moreover, these haemocytes displayed lower PKC and ERK activity when compared to those from uninfected snails.…”
Section: Immune Responses Of L Stagnalis During T Szidati Infectioncontrasting
confidence: 75%
“…Moreover, these haemocytes displayed lower PKC and ERK activity when compared to those from uninfected snails. Considering the regulatory role of these pathways in haemocyte defence processes, this suggests how the parasite may achieve suppression of haemocyte defence activities in infected snails (Skála et al, 2014). In addition, the size distribution of circulating haemocytes in L. stagnalis was unaffected by T. szidati as revealed by flow cytometry at two, four, six, and eight weeks p.i.…”
Section: Immune Responses Of L Stagnalis During T Szidati Infectionmentioning
confidence: 94%
See 1 more Smart Citation
“…1H). This finding was unexpected because PMA induces the respiratory burst in R. lagotis haemocytes (Skála et al, 2014), a reaction considered essential for ET-like fiber formation (Robb et al, 2014;Poirier et al, 2014).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Experiments with P. corneus were also conducted in Chernin´s balanced salt solution (CBSS; Chernin, 1963). Haemolymph from R. lagotis was handled as described previously (Skála et al, 2014). The haemocyte number per well was approx.…”
Section: Snails and Haemocytesmentioning
confidence: 99%